The narcissism epidemic : living in the age of entitlement - Twenge, Jean M., 1971-; Campbell, W. Keith (New York : Free Press, 2010)
Citing a rise in such factors as cosmetic surgery, status-related debt, and misrepresented Facebook profiles, a cautionary report on the increase of unhealthy ego-related behaviors examines its actual cost to families, organizations, and societies.
Includes bibliographical references (p. 309-320) and index.
Keywords: Narcissism -- United States; Entitlement attitudes -- United States